2010
DOI: 10.3109/13697131003675922
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone treatment of HSDD in naturally menopausal women: the ADORE study

Abstract: TTP was effective in treating HSDD and improving sexual function in this study of naturally menopausal women with and without concurrent hormone therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(67 citation statements)
references
References 22 publications
1
63
0
2
Order By: Relevance
“…In another study, the ADORE study, 272 postmenopausal women, the majority of whom were not receiving hormone replacement, were randomized to transdermal testosterone 300 μg daily or placebo for 6 months. The group receiving testosterone reported increased satisfying sexual episodes, improvements in sexual desire, and reduction of distress compared with placebo at the study end point [40]. A group of surgically postmenopausal women with a diagnosis of HSDD were given either 150, 300, or 450 μg daily transdermal testosterone for 24 weeks in addition to estradiol replacement, and the women receiving the two higher doses of testosterone had improvement in sexual desire and frequency of sexual activity compared with the placebo group [41].…”
Section: Interventions For Treatment-emergent Sexual Dysfunction Withmentioning
confidence: 95%
“…In another study, the ADORE study, 272 postmenopausal women, the majority of whom were not receiving hormone replacement, were randomized to transdermal testosterone 300 μg daily or placebo for 6 months. The group receiving testosterone reported increased satisfying sexual episodes, improvements in sexual desire, and reduction of distress compared with placebo at the study end point [40]. A group of surgically postmenopausal women with a diagnosis of HSDD were given either 150, 300, or 450 μg daily transdermal testosterone for 24 weeks in addition to estradiol replacement, and the women receiving the two higher doses of testosterone had improvement in sexual desire and frequency of sexual activity compared with the placebo group [41].…”
Section: Interventions For Treatment-emergent Sexual Dysfunction Withmentioning
confidence: 95%
“…We analyzed the ten studies included in the Alexander et al (2004) review, focusing specifically on circulating hormone levels produced by treatment and their relationship to sexual desire. In addition, we analyzed five studies excluded from Alexander et al (2004) because they were not double-blind randomized controlled trials (Burger et al, 1987; Davis et al, 1995; Dow et al, 1983; Sarrel et al, 1998; Sherwin & Gelfand, 1987), and eight double-blind randomized controlled trials published after 2004 that investigated the effects of estrogen and/or androgen therapies on sexual desire in postmenopausal women (Braunstein et al, 2005; Buster et al, 2005; Davis et al 2006a, 2006b; 2008; Panay et al, 2010; Shifren et al, 2006; Simon et al, 2005). Table 1 provides details of all studies included in the following review.…”
Section: Hormone Therapies For Low Libido In Postmenopausal Womenmentioning
confidence: 99%
“…Ten double-blind randomized controlled trials have compared the effectiveness of an estrogen therapy alone and in combination with testosterone at increasing sexual desire in postmenopausal women (Braunstein et al, 2005; Buster et al, 2005; Davis et al, 2006b; Floter et al, 2002; Lobo et al, 2003; Panay et al, 2010; Sarrel et al, 1998; Shifren et al, 2000; 2006; Simon et al, 2005). Sarrel et al (1998) administered an esterified estrogen (EE) therapy by itself or in combination with methyltestosterone to postmenopausal women, and reported that neither treatment increased sexual desire as compared to baseline.…”
Section: Hormone Therapies For Low Libido In Postmenopausal Womenmentioning
confidence: 99%
“…These women are also candidates for testosterone therapy. [53][54][55] There are currently no female testosterone therapies registered or available in South Africa (SA). Tibolone, which has weak androgenic, oestrogenic and progestogenic activity and does not increase sex hormone binding globulin, can be used as an alternative to testosterone.…”
Section: Androgen Therapymentioning
confidence: 99%